Legal Effectiveness Strategy for Drafting Democratic Village Regulations - Mukhammad Soleh (LEGAL BRIEF, 2022)
The Village Community has the right to give their opinion on the Village Regulation Draft”. Whether ithe law implementation in community empowerment participating iand idiscussion iof the iVillage iRegulation iDraft ion iPleret iVillage iRevenue iand Expenditurei Budget, Pohjentrek District, Pasuruan Regency, Indonesia, effective and implemented well. Thei purposei of ithis iresearch is to find effective village regulation-making strategies. This studyi usesi a inon-doctrinal ilegal study imethod, collection ithrough literature study and interviews, iusing iqualitative ijuridical analysisi methods. iThe iconclusion iof ithe iresearch iis ithat. The effectiveness strategy for drafting democratici village iregulations are First, the Socialization of legal methods. Second, Provision of a sufficient budget. Third, Good Time for implementation. Fourth, Imposing strict punishment for a delay in stipulating village regulations.